PEMASARAN DIGITAL DI PENDIDIKAN ISLAM: MEMBANGUN LOYALITAS SISWA MELALUI STRATEGI PERIKLANAN YANG SESUAI SYARIAH - Muhammad Thoiful Abrar; Muhammad Kholilurrohman; Zackyl Musthofa; Unzilah Khomairohtus Shiyamah; Ida Kusumawati; Siti Khofsah; Hefniy (Jurnal Manajemen Pendidikan, 2026)
This research aims to explore the application of sharia-based digital marketing strategies in Islamic education and its impact on student loyalty. This research focuses on how marketing strategies aligned with sharia principles can build long-term relationships between educational institutions and students, as well as increase their loyalty. The method used is a qualitative approach with in-depth interviews and observations of management and students. The results of the study show that digital marketing that prioritizes Islamic moral values, such as honesty and character development, can increase student loyalty by strengthening a sense of trust and attachment to institutions. Sharia-based marketing also manages to avoid the element of materialism and focuses more on the quality of education and character of students. The implications of this study show the importance of Islamic educational institutions to implement marketing strategies in accordance with sharia principles in order to strengthen student loyalty and create a positive image of the institution. This research also contributes to the development of educational marketing theories based on Islamic values that can be applied in other Islamic educational institutions.